Big Data Analysis: Concepts, Challenges And Opportunities (International Journal of Innovative Research in Computer Science & Technology, 2020)
Big Data has the potential to bring valued  insights for advanced decision making. It has become a  trending practice to adopt Big Data into their process. It has  attracted both the academicians as well as the industry  people. A voluminous amount of diverse data is generated  every day, and Big Data has emerged as an approach to  process them. Data can be analysed in a different manner  depending upon the requirement. The paper identifies the  challenges and issues associated with Big Data and points  out the research and industry opportunities in this field.
Keywords: Big Data Analytics; Big Data Challenges; Big Data Lifecycle; Big Data Opportunities